1999
DOI: 10.1007/pl00007646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Terbutaline on Exercise Capacity and Pulmonary Function in Patients with Chronic Obstructive Pulmonary Disease

Abstract: The objective of this study was to investigate the effects of a single dose of a beta2-agonist, terbutaline (Bricanyl Turbuhaler), on resting lung function and exercise capacity in patients with chronic obstructive lung disease. Using a double-blind, placebo-controlled, randomized crossover study and outpatients from a department of pulmonary medicine at a major inner-city hospital, we examined 26 individuals with chronic obstructive lung disease who met the criteria of 40% Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…The mechanisms involved are not clear, although it is known that some fuel-cell CO analysers are sensitive to exhaled ethanol and ketones. In obstructive lung disease subjects, after administration of a bronchodilator, DL,CO may increase up to 6% [87]. Bronchodilators can affect VA, vasomotor tone, etc., and their use prior to testing could conceivably optimise these factors.…”
Section: Miscellaneous Factorsmentioning
confidence: 99%
“…The mechanisms involved are not clear, although it is known that some fuel-cell CO analysers are sensitive to exhaled ethanol and ketones. In obstructive lung disease subjects, after administration of a bronchodilator, DL,CO may increase up to 6% [87]. Bronchodilators can affect VA, vasomotor tone, etc., and their use prior to testing could conceivably optimise these factors.…”
Section: Miscellaneous Factorsmentioning
confidence: 99%
“…This observation confirms the bronchodilator effect of ISABA treatment in COPD observed in several acute studies. [19][20][21][22] None of the included studies was designed to investigate changes in bronchodilator activity over time, and our data show no evidence for the hypothesis that this activity is attenuated by chronic treatment with ISABA. The short duration of the included studies in this review made them unsuitable for evaluating any effect on disease progression over time.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies demonstrated that 2.5 mg and 1.5 mg terbutaline significantly increased DL,CO in patients with chronic obstructive pulmonary disease and normal subjects. 3,4 However, other studies did not detect any difference in DL,CO after 200 mg salbutamol in obstructive patients 5 and 18 mg tiotropium in normal subjects. 6 Baldi et al 7 investigated the effect of incremental doses of salbutamol on DL,CO in patients with chronic obstructive pulmonary disease and found that DL,CO increased progressively with the dose, and the increase became significant at the highest dose of 1000 mg.…”
Section: Introductionmentioning
confidence: 88%
“…The published literature gives conflicting results. Two studies demonstrated that 2.5 mg and 1.5 mg terbutaline significantly increased D L ,CO in patients with chronic obstructive pulmonary disease and normal subjects . However, other studies did not detect any difference in D L ,CO after 200 μg salbutamol in obstructive patients and 18 μg tiotropium in normal subjects .…”
Section: Introductionmentioning
confidence: 97%